Digital watermarking - Cox, I. J. (Ingemar J.); Miller, Matthew L.; Bloom, Jeffrey A. (Jeffrey Adam), 1964- (San Diego, CA : Academic Press, 2001)
Digital watermarking is a key ingredient to copyright protection. It provides a solution to illegal copying of digital material and has many other useful applications such as broadcast monitoring and the recording of electronic transactions. Now, for the first time, there is a book that focuses exclusively on this exciting technology. Digital Watermarking covers the crucial research findings in the field: it explains the principles underlying digital watermarking technologies, describes the requirements that have given rise to them, and discusses the diverse ends to which these technologies are being applied. As a result, additional groundwork is laid for future developments in this field, helping the reader understand and anticipate new approaches and applications. * Emphasizes the underlying watermarking principles that are relevant for all media: images, video, and audio. * Discusses a wide variety of applications, theoretical principles, detection and embedding concepts and the key properties of digital watermarks--robustness, fidelity, data payload, and security * Examines copyright protection and many other applications, including broadcast monitoring, transaction tracking, authentication, copy control, and device control. * Presents a series of detailed examples called "Investigations" that illustrate key watermarking concepts and practices. * Includes an appendix in the book and on the web containing the source code for the examples. * Includes a comprehensive glossary of watermarking terminology.
Applications and properties -- Models of watermarking -- Basic message coding -- Watermarking with side information -- Analyzing errors -- Using perceptual models -- Robust watermarking -- Watermark security -- Content authentication.
Includes bibliographical references (p. 501-519) and index.
Keywords: Computer security; Digital watermarking; Data protection; Electronic books